2018
DOI: 10.1080/13880209.2017.1391298
|View full text |Cite
|
Sign up to set email alerts
|

Zanthoxylum alatum abrogates lipopolysaccharide-induced depression-like behaviours in mice by modulating neuroinflammation and monoamine neurotransmitters in the hippocampus

Abstract: Context: Depression is an inflammatory, commonly occurring and lethal psychiatric disorder having high lifetime prevalence. Zanthoxylum alatum Roxb. (Rutaceae), commonly called Timur, has high medicinal value and is used ethnomedicinally for the treatment of various diseases.Objective: To evaluate the effect of hexane extract of Z. alatum seeds (ZAHE) on lipopolysaccharide (LPS)-induced depression-like behaviour in Swiss albino mice.Materials and methods: Mice were treated with ZAHE (100 and 200 mg/kg, p.o.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…In the hippocampus, a decrease of NA is associated with mental impairments such as a decrease of activity, depression and cognitive dysfunction [18][19][20]33]. In the present study, hippocampal NA level was decreased 24 hours after surgical stress.…”
Section: Discussionsupporting
confidence: 57%
“…In the hippocampus, a decrease of NA is associated with mental impairments such as a decrease of activity, depression and cognitive dysfunction [18][19][20]33]. In the present study, hippocampal NA level was decreased 24 hours after surgical stress.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the present results are in line with those of previous studies using CMS mice ( 17 , 31 , 32 ). It has been shown that abnormal levels of monoamine neurotransmitters are a typical feature of depression and stress in animals, and have been proposed as the principal pathogenic factor involved in this condition ( 10 ). The present results indicated that the levels of neurotransmitters, 5-HT and NE, decreased significantly after CMS exposure, which is consistent with previous studies ( 3 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inflammatory cytokines impair neurogenesis, activity of neurotrophic factors and neuronal plasticity ( 8 , 9 ). Inflammatory cytokines have been proposed to regulate monoamine neurotransmitter metabolism by inhibiting neurotransmitter synthesis and promoting monoamine neurotransmitter hydrolysis ( 10 , 11 ). Therefore, inhibiting inflammation may be a potential therapeutic strategy for depression ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The behavioural as well as biochemical and molecular studies have shown that the seed of the plant possesses significant antidepressant property. 31…”
Section: Antidepressant Activitymentioning
confidence: 99%